Analysis of the Meaning and Function of Huler Wair Ceremony in Waiara Village, Kewapante District Sikka Regency - Agustina Yuliovi; Darmawan Darmawan; Antonius M. K. Naro (Indo Publishing, 2026)
This research is titled